Ethics Project Mata Kuliah Etika Kristen dalam Meningkatkan Keterampilan Berpikir Kritis Mahasiswa Indonesia - Irvan Sabelau; Andrika Telaumbanua (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
The project shows that Christian ethical principles provide a strong foundation for Indonesian students to understand values such as 1) love, 2) justice, and 3) responsibility, which can help Indonesian students improve their critical thinking skills. The purpose of this study is to explore the impact of the ethics project in the Christian Ethics course on improving the critical thinking skills of Indonesian students. The methods used include active learning through discussions, case studies, and social projects that integrate Christian ethical values. As such, the results of the evaluation showed that there was a significant improvement in Indonesian students' ability to analyze and formulate ethical decisions. Thus, this project contributes to the formation of a generation of students who are more sensitive to ethical and social issues in societ.